THE EFFECT OF COMMENTARY STRATEGY TOWARDS STUDENTS’ SELF-CONIDENCE IN SPEAKING ABILITY - safari, agus (Journal of Languages and Language Teaching, 2016)
This research was aimed to find out or not Commentary Strategy has significant effect in teaching speaking, and has correlation students self-confidence and their speaking ability. The research was quasi- experimental method and design was non equivalent control group design. The population of this research was the whole students of second grade students of MA NW AIKMEL, the total population is 43 students that consisted of two class. The sample was taken from of the second grade  students which  consisted of 43 students. The data were gained from pre-test and post-test of oral  and questionnaire. The instrument was in form of test and questionnaire. In analyzing the data, t-test formula was used. The finding showed that the mean score of post-test for experimental is ( 60,70 ) higher than control ( 49,61 ). Further, the result of t-test showed  ( 1,76 ) is higher than t-table ( 1.684 ) with the degree of freedom (df) = 95 at the significant level  = 0. 05. It mean that the alternative Hypothesis  ( Ha) was accepted and Null Hypothesis  was rejected . and  then there is correlation between students self-confidence and their speaking ability, it was found in experimental group r-test showed r is higher than the r table (r= 0,791 ≥ rt = 0, 444) and  for control group r-test showed r is higher than the r table ( r =  0, 482 ≥ rt = 0, 0,444). So it can be concluded that commentary strategy has significant effect towards students self-confidence in speaking ability and there is correlation between students self-confidence and their speaking ability at the second grade students of MA NW AIKMEL in academic year 2016/2017.